Perkembangan Trasportasi Darat, Laut serta Udara di Kota Surabaya pada Awal Abad ke-20 - zahir, Zahir (UIN Sunan Gunung Djati Bandung, 2023)
The development of transportation modes is one of the keys to developing a region towards modernity. The development of modes of transportation always moves in line with technological developments in its time, making the emergence of transportation, whether land, sea or air, always a marker of progress and modernization of a country or region. In the city of Surabaya, the emergence of modern modes of transportation is a support for city mobilization which relies on the industrial and economic sectors. The city of Surabaya is developing because the economic sector is increasingly growing with the emergence of various forms of transportation that are driving the mobility of people and goods that connect the city of Surabaya with its supporting areas and other areas. The development of transportation in this city is also a sign of the increasingly advanced city of Surabaya from the end of the 19th century to the beginning of the 20th century, which was based on the applied technology and industrial sectors. Transportation advances are not only limited to supporting the economic sector, but are also used for administrative and military purposes in the city of Surabaya.